2012
DOI: 10.1155/2012/712536
|View full text |Cite
|
Sign up to set email alerts
|

The Janus Face of Lipids in Human Breast Cancer: How Polyunsaturated Fatty Acids Affect Tumor Cell Hallmarks

Abstract: For several years, lipids and especially n − 3 and n − 6 polyunsaturated fatty acids (PUFAs) receive much attention in human health. Epidemiological studies tend to correlate a PUFA-rich diet with a reduced incidence of cancer, including breast cancer. However, the molecular and cellular mechanisms supporting the effect of PUFAs in breast cancer cells remain relatively unknown. Here, we review some recent progress in understanding the impact that PUFA may have on breast cancer cell proliferation, apoptosis, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 110 publications
1
36
1
Order By: Relevance
“…The ratio of n-6 to n-3 PUFA present in tumors plays a critical role in biophysical organization of membranes and lipid rafts changing oncogenic receptor localization (43-45), enhancing supply of proinflammatory LA and AA for eicosanoid and prostaglandin synthesis (46,47), and promoting breast cancer cell migration, invasion and metastasis (44). Recently, dietary fish oil n-3 FA were shown to inhibit mammary tumor progression in obese ovariectomized mice, possibly by lowering adipose inflammation and activating c-JNK to inhibit proliferation and initiate apoptosis (48).…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of n-6 to n-3 PUFA present in tumors plays a critical role in biophysical organization of membranes and lipid rafts changing oncogenic receptor localization (43-45), enhancing supply of proinflammatory LA and AA for eicosanoid and prostaglandin synthesis (46,47), and promoting breast cancer cell migration, invasion and metastasis (44). Recently, dietary fish oil n-3 FA were shown to inhibit mammary tumor progression in obese ovariectomized mice, possibly by lowering adipose inflammation and activating c-JNK to inhibit proliferation and initiate apoptosis (48).…”
Section: Discussionmentioning
confidence: 99%
“…Very low intake of both ω-3 and ω-6 PUFAs could result in a high ratio value for ω-3/ω-6 intake (when ω-6 intake is less than 1). Doses in excess of 2 g/day may be required for decreasing prostaglandin E2 production [58,59], a primary inflammatory eicosanoid resulting from AA metabolism, which has been implicated in carcinogenesis [7]. Thus, a high ratio of ω-3/ω-6 derived from low intakes of ω-3 and ω-6 PUFAs may not represent a sufficient dose for ω-3 to exert a beneficial response in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory studies show that ω-3 PUFAs competitively inhibit ω-6 fatty acids, thus lowering levels of inflammatory eicosanoids generated from ω-6 metabolism [7], and that higher ω-3 relative to ω-6 could reduce breast cancer through inflammation, oxidative stress, and estrogen metabolism [710]. Asian populations have a substantially higher ratio of ω-3/ω-6 intake compared to European and U.S. populations [11,12], due to higher fish consumption [1315], which may partially explain the lower breast cancer risk observed in these populations [1619].…”
Section: Introductionmentioning
confidence: 99%
“…the pro-apoptotic effect of DHa on cancer cells and especially in breast cancer is well known (11). However, few studies have also shown the inhibitory effect of DHa on the metastatic and invasive potential of cancer cells (9,27,28).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that DHa not only acts as an anti-proliferative agent by lengthening the cell cycle between the G2/M transition (8), but also it is capable of inducing apoptosis and reducing the invasive potential of the triple-negative breast cancer cell line MDa-MB-231 with an optimal amount of 100 µM (9). DHa can modify the metastatic phenotype of cancer cells, emphasizing the anti-cancer potential of the omega-3 (n-3) Pufas (10,11). this anti-cancer activity of DHa is promising and could partly result in a modification of the lipid contents of the plasma membrane and its fluidity (12).…”
Section: Introductionmentioning
confidence: 99%